Assessment by surface electromyography and therapeutic exercise in non-specific chronic low back pain. Pilot study - Caña-Pino, Alejandro; Navarro-Escribano , Jorge; Apolo-Arenas, Mª Dolores (MHSalud: Revista en Ciencias del Movimiento Humano y Salud, 2025)
Introduction: Chronic low back pain (CLBP) is a common and disabling disorder in Western society. The use of objective methods for its assessment is relevant because they include indicators that subjective methods do not, and thus have greater reliability and applicability. Surface electromyography seems to be useful and easy to use to objectively analyze lumbar muscle activity. Objective: (1) To evaluate in subjects with DLCI the muscular activity of lumbar spinal erectors and multifidus by means of surface electromyography; and (2) to evaluate the efficacy of a therapeutic exercise program on clinical variables such as pain, disability and kinesiophobia. Methods: 3 subjects with chronic low back pain were evaluated before and after a therapeutic exercise program with electromyography, algometer, NPRS scale, Roland Morris questionnaire and TAMPA scale (TSK-11). Results: after treatment, in the flexion-relaxation phenomenon (FFR), the root mean square (RMS) decreases, but the maximum voluntary contraction (MCV) increases in erectors and decreases in multifidus; in addition, 2 of the participants presented electromyographic silence. The exercise program is effective in reducing pain, disability and kinesiophobia; and the pain threshold to pressure increased. Conclusions: RMS, MCV and electromyographic silence in the FFR could be useful electromyography indicators to quantify therapeutic interventions in subjects with CLBP and could have clinical applicability. However, studies with a sufficiently large sample size are needed to establish reliable results.